Japanese law on Gender change - Nguyen Thi Phuong, Cham (VNU Journal of Science: Legal Studies, 2017)
After the Civil Code 2015 (Civil Code 2015) takes effect from January 1 st 2017, the first Vietnamese law recognizes sex change. However, there are still many legal issues that can not be resolved. At the same time, there is requirements to develop a relevant law so that these provisions of the Civil Code 2015 come into social life. This article studies Japanese law on gender change from a theoretical and practical point of view, thus proposing the scope of regulation and structure of the relevant laws on this issue in Vietnam in the future.